PENGARUH KINERJA DAN DAYA SAING KOPERASI SYARI’AH TERHADAP PERTUMBUHAN UMKM DI PROVINSI - Sholihah, Marwatus; Setiawan, Iwan; Jamaludin, Jujun (Likuid Jurnal Ekonomi Industri Halal, 2021)
This study aims to determine the effect of the performance and competitiveness of sharia cooperatives on the growth of SMEs in Lampung Province which is seen from the indicators of the remaining business results of sharia cooperatives and the volume of business of sharia cooperatives in Lampung Province. This study uses a descriptive quantitative approach with the type of library research (Library Research). The type of data used is secondary data, namely data on the development of the remaining business results and business volume of sharia cooperatives sourced from the official website of the Lampung Province Cooperatives and UMKM and the growth of SMEs sourced from the official website of the Central Statistics Agency of Lampung Province using the saturated sampling method as Sampling techniques and data analysis methods include classical assumption test, multiple linear regression, t-test, f-test and determination test (R2). The results of the analysis obtained that the Performance and Competitiveness of Syari'ah Cooperatives had a significant effect simultaneously on the growth of MSMEs in Lampung Province is 50.3% while the remaining 49.7% is influenced by other variables or factors outside of this study.Keywords : Performance, Competitiveness, Sharia Cooperatives, UMKM, Lampung Province